2021
DOI: 10.18502/sjms.v16i3.9698
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Adherence to COVID-19 Preventive Measures: A Continental Review

Abstract: Background: The burden of the novel coronavirus disease (COVID-19) has been on the rise since it was first reported in December 2019. COVID-19 has devastated global economy, public health, social interaction, and has claimed millions of lives globally within a few months. Due to the severe effect of some of the instituted guidelines on citizens and the economy, some of the policies in place to curtail the spread were receded. Hence, the present review aims to assess existing literature on the knowledge and adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…This finding contradicts the findings of previous studies, which found that having adequate knowledge resulted in higher adherence [ 51 , 52 ]. However, other studies suggested that adequate knowledge does not always result in higher adherence [ 53 ]. Knowledge alone may not be enough to influence compliance.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contradicts the findings of previous studies, which found that having adequate knowledge resulted in higher adherence [ 51 , 52 ]. However, other studies suggested that adequate knowledge does not always result in higher adherence [ 53 ]. Knowledge alone may not be enough to influence compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite showing a high level of awareness of the disease, most individuals have been reported to have poor practices regarding infection prevention and adherence to the recommended measures [37] [38]. Similarly, there have been reports of a lack of translation of being knowledgeable regarding COVID-19 and adherence to the recommended preventive measures [39]. Non-adherence to these guidelines predisposes individuals to contracting COVID-19 [34] [37].…”
Section: Adherence To Covid-19 Prevention Measures Across Populations...mentioning
confidence: 99%
“…Prior to the development and approval of COVID-19 vaccines, adherence to the preventive measures has been pivotal in preventing viral transmission [6]. Since the onset of vaccine roll-out, vaccination has proved to be one of the best measures to curtail the spread and transmission of COVID-19.…”
Section: Willingness To Be Vaccinated -Contributory Factorsmentioning
confidence: 99%
“…Coronaviruses are a family of viruses that cause mild to moderate upper-respiratory tract illnesses. Six (6) variants of this highly diverse family namely, 229E, NL63, OC43, HKU1, SARS-CoV, and MERS-CoV have been reported to cause mild to severe respiratory tract infections in humans [1]. The novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative infectious agent of the novel coronavirus disease (COVID-19) was first reported from Wuhan city of China in December, 2019 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation